Multi-user detection for CPM spread system with turbo in VDES. Issue 1 (1st November 2022) - Wu, Feiyu; Zhang, Qianwu; Xiang, Qian; Yin, Huihui; Zhang, Xiyan
Abstract: The multi-user detection technology uses the spread sequence, delay, amplitude and phase information of each user to jointly detect users, which can effectively suppress multiple access interference, It is one of the key technologies in satellite communication system to make full use of uplink spectrum resources and improve system performance and capacity. Continuous phase modulation spread signal can adapt to multi-user communication due to the random variation of spread sequence, which is gradually applied to satellite communication. QPSK-CPM spread modulation scheme is adopted in the random access channel of VHF data exchange system. Aiming at the multi-user detection problem of QPSK-CPM spread system, proposing a multi-user detection algorithm based on interference elimination joint Turbo iterative detection based on the characteristics of CPM spread sequence. Compared with the traditional serial interference cancellation algorithm, the algorithm can effectively eliminate the multiple access interference problem caused by user aliasing by using the characteristics of Turbo codes. The theoretical simulation shows that the algorithm has a good detection effect on multi-user aliased signals.